História concisa do sindicato dos professores do ABC (1984-1990) - Moraes, Carin Sanches de (2019)
Imbricated in the discussions on the associativism and unionism of the education workers, mainly referring to the contributions this issue can bring to the Brazilian educational history, we aim, with this research, to recover some aspects of the social and political trajectory of the Teachers` Union of ABC. Fundamentally, we sought to understand the existing contradictions in the process of establishment and consolidation of this union, which represents the group of workers from the teaching private sector in this densely populated metropolitan region of Brazil. The research aims to reassemble its historical trajectory starting with the initiative of a group of teachers who were inserted in the mobilizations that happened in the 1970s and 1980s due to the policies implemented by the military civil dictatorship that historically took place at that moment. In 1984, the Teacher’s Professional Association of ABC was founded (APRO-ABC) and years later, on March 13th, 1986, the SIMPRO ABC received its Union Register. The course of this entity was guided by classist attitudes as we can see in the case of the strike support given by other categories workers of the region, the pioneer affiliation, among the private educational entities, to the Unique Worker’s Central (CUT) and even in campaigns of massification of afilliations of associates shown in slogans such as “Educating is a political act, unionizing, too!”The research was based on interviews with teachers who taught at the schools of the cities that constitute the known ABC Paulista and on the syndical directors and activists acting there in the studied period and also on their newsletters and journals, as we aim to seek difficulties overcoming, theoretical and methodological, mainly caused by the substantial lack of studies on the political and organizational efforts of the education workers who function in the private sector.